Abstract--In Support of By-Law 5-1-(j) - Browning, Charles (My University, 1985)
This is a commentary to support the byaw 5-1-(j) which was Proposition 48 and to make adjustments to it to support athletes' educational and personal development.
Keywords: eligibility; scholarships